2021
DOI: 10.3389/fimmu.2021.734646
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Multi-Omics Identification of Interferon-γ Response Characteristics Reveals That RBCK1 Regulates the Immunosuppressive Microenvironment of Renal Cell Carcinoma

Abstract: Interferon-gamma (IFN-γ) has a complex role in modulating the tumor microenvironment (TME) during renal cell carcinoma (RCC) development. To define the role of IFN-γ response genes in RCC progression, we characterized the differential gene expression, prognostic implications, and DNA variation profiles of selected IFN-γ response signatures, which exhibited a significant hazard ratio for the overall survival (OS) and progression-free survival (PFS) of papillary, chromophobia, and clear cell RCC (ccRCC) patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Increasing evidence suggests that the malignant behaviors and treatment resistance of cancers are heavily governed by the crosstalk between the TME and tumor cells 28 . Chemokines are crucial in modulating the activity and tolerance status of tumors, as well as the abundance and cellular differentiation of TILs involved in pro-and anti-tumorigenic immune activities [29][30][31][32] . Previous studies found high CCL5 expression in PBRM1 MUT ccRCC patients that exhibited poor clinical outcomes and increased mast cell infiltration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence suggests that the malignant behaviors and treatment resistance of cancers are heavily governed by the crosstalk between the TME and tumor cells 28 . Chemokines are crucial in modulating the activity and tolerance status of tumors, as well as the abundance and cellular differentiation of TILs involved in pro-and anti-tumorigenic immune activities [29][30][31][32] . Previous studies found high CCL5 expression in PBRM1 MUT ccRCC patients that exhibited poor clinical outcomes and increased mast cell infiltration 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Most tumors arise and develop under strong evolutionary pressures imposed by factors such as nutrition, metabolism, immunity, and therapy. These pressures promote the diversification of the tumor microenvironment, ultimately leading to a degree of inherent tumor heterogeneity that enables disease progression and drug resistance ( 45 ). To validate the immunophenotype, 42 patients with BCa receiving immunotherapies were enrolled from the FUSCC cohort, and expression patterns of three CDI hub genes (DRD5, SCL2A14, and IGF1) were detected using IHC staining analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previous studies have revealed a markedly negative correlation between RNF31 expression and survival time in a variety of cancer types, such as prostate [ 19 ], breast [ 21 ], gastric [ 16 ], and colon cancers [ 20 ]. In addition, RBCK1 is highly expressed in pulmonary adenocarcinoma [ 23 ], breast cancer [ 24 ], colon cancer [ 25 ], and renal cell carcinoma [ 26 , 27 ]. These observations agree with our findings, suggesting that RNF31 and RBCK1 may be used as prognostic markers in patients with HCC.…”
Section: Discussionmentioning
confidence: 99%
“…RBCK1 is an RBR E3 ligase [ 22 ]. RBCK1 has been reported to be overexpressed in lung adenocarcinoma [ 23 ], breast cancer [ 24 ], colorectal cancer [ 25 ], and renal cell carcinoma [ 26 , 27 ], where high RBCK1 expression correlates with an unfavorable prognosis. RBCK1 promotes tumor progression through several mechanisms.…”
Section: Introductionmentioning
confidence: 99%